DETERMINANTS OF CORPORATE EFFECTIVE TAX RATE: EVIDENCE FROM INDONESIA - Ardiansyah, Benny Gunawan; Lumban Gaol, Geby Agnes Lumban Gaol (IPSAR (International Public Sector Accounting Review), 2024)
The phenomenon in developed countries shows that the Effective Tax Rate (ETR) is much lower than the Statutory Tax Rate (STR), whereas in Indonesia it is the opposite. The main cause is that ETR and STR are determined by different variables in their calculations. This study will conduct an analysis of the variables that influence the amount of ETR in Indonesia: capital intensity, inventory intensity, and leverage. The research was conducted using a quantitative multiple linear regression method with a panel data structure in the form of company data listed on the IDX during the 2011-2019 period (before Covid-19 pandemic).The results showed that capital intensity did not have a significant effect on ETR. Every 1 percent increase in capital intensity will result in an increase in the effective tax rate of 1.8 percent. Inventory intensity has a significant and negative effect on the corporate effective tax rates. Every 1 percent increase in inventory will result in a 10.6 percent decrease in the effective tax rate. Leverage has a significant and positive effect on the corporate effective tax rate. Every 1 percent increase in leverage will result in an increase in the effective tax rate of 5.7 percent. Keywords: effective tax rate, capital intensity, inventory intensity, leverage